PENGARUH PUPUK ORGANIK GULMA SIAM (Chromolaena odorata) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA (Lactuca sativa L) - Bayu Nugroho; Nikmah Musa; Yunnita Rahim (Universitas Negeri Gorontalo, 2022)
This study aims to determine the growth and yield of lettuce with the application of Siam weed (Chromolaena odorata) organic fertilizer. This research was conducted in North Huntu Village, South Bulango District, Bone Bolango Regency, Gorontalo Province from August to November 2020. The design used was a randomized block design with 4 treatments of siam weed organic fertilizer, namely: P0 = control, P1 = 10 t ha-1, P2 = 20 t ha-1, and P3 = 30 t ha-1. Parameters observed were plant height, number of leaves and plant fresh weight. The data were analyzed using analysis of variance (ANOVA), then further test was carried out at 5% level of least significant different (LSD). The results showed that the application of Siam weed organic fertilizer had an effect on the growth and yield of lettuce plants, including plant height, number of leaves and plant fresh weight. The best dosage that effect on the growth and yield of lettuce was 30 t ha-1.Keywords: fertilizer, siam weed, lettuce